CRITERION FOR IDENTIFICATION OF THE PROBABILITY MODEL OF THE STATE OF SATELLITE COMMUNICATION CHANNELS - G. I. Linets; S. V. Melnikov (Современная наука и инновации)
Predictive methods and models are used to identify the state of satellite communication channels. However, they evaluate their condition only at a qualitative level, which does not allow fine-tuning the characteristics and parameters of satellite channels. Such models and methods cannot provide reliable identification of the States of satellite communication channels and quickly determine changes in the distribution laws of random variables associated with the appearance of small-scale inhomogeneities in the case of dynamic changes in the ionospheric layer, which is typical for rapid fading of GPS/GLONASS signals.